ER-mitochondria tethering and its signaling: A novel therapeutic target in breast cancer - Chamanthi Paidi; Yerusha Nuthalapati; Anuveda Sree Samudrala; Priyamvada Bhamidipati; Charanteja Mangam; Danny R. Welch; Ganji Purnachandra Nagaraju; RamaRao Malla (Molecular Therapy: Oncology)
Communication between the endoplasmic reticulum (ER) and mitochondria through mitochondria-associated ER membranes (MAMs) is assisted by tethering proteins and signaling pathways, manifesting the dynamic exchange of lipids, calcium, and signaling molecules. However, dysregulation of tethering and signaling proteins contributes to the progression of breast cancer (BC). Abnormal MAM structures and altered ER-mitochondrial tethering impair mitochondrial functions and thereby drive BC progression. Altered mitochondrial dynamics, often characterized by dysregulated dynamin-related protein 1 (Drp1) and mitofusin-2 (Mfn2) activity, enhances BC cell survival. Similarly, ER stress and the unfolded protein response, both modulated by dysregulated ER-mitochondrial contacts, promote drug resistance. In BC, caveolae-dependent and -independent caveolin-1 signaling alongside Yes-associated protein (YAP) signaling pathway alters organelle dynamics by interacting with Drp1 and Mfn2, underscoring their therapeutic potential. This review explores potential therapeutic strategies targeting ER-mitochondrial communications and their potential for hindering BC progression. These strategies include modulating mitochondrial dynamics and promoting controlled ER stress by disrupting aberrant ER-mitochondrial tethering using chemotherapeutics, clinical inhibitors, and natural compounds, alone or in combination. Ultimately, targeting dysregulated ER-mitochondrial tethering has significant potential to improve patient outcomes in BC.